2006
DOI: 10.1002/jbm.b.30688
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating aging of zirconia femoral head implants: Change of surface structure and mechanical properties

Abstract: Recently, alternations of zirconia ceramic femoral heads of total hip prostheses during in vivo conditions have caused concern in the medical disciplines regarding phase transformation of zirconia prosthetic components. In this paper, we have investigated the mechanical and structural properties of different laboratory aged zirconia femoral heads and correlated changes in mechanical properties with the phase compositions of the sample. From laser microscope observation, cross-sectional Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
2
28
1
3
Order By: Relevance
“…Another parameter studied by these researchers is the Young's modulus. These studies as well as that of Chowdhury et al [29] demonstrate a gradual decrease of Young's modulus with increasing temperature. This finding opposes the results of the present study that show an increase of the modulus after aging.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Another parameter studied by these researchers is the Young's modulus. These studies as well as that of Chowdhury et al [29] demonstrate a gradual decrease of Young's modulus with increasing temperature. This finding opposes the results of the present study that show an increase of the modulus after aging.…”
Section: Discussionsupporting
confidence: 66%
“…This finding opposes the results of the present study that show an increase of the modulus after aging. However it must be noted that in the study of Chowdhury et al [29] the modulus decreased in specimens with concentration of monoclinic crystals over 10%. The specimens that underwent aging and bending test in the present study had a percentage of monoclinic phase of not more than 4%.…”
Section: Discussionmentioning
confidence: 83%
“…At this rate, the researchers concluded that the performance of ceramic-polyethylene wear couples should be unaffected for the lifetime of most patients. Yet, retrievals as well as in vitro studies showed considerable changes in surface finish in some particular heads [77,453]. The apparent contradiction in performance between in vitro and in vivo Y-TZP femoral heads was likely due to higher in vivo stresses which were not addressed nor replicated in the laboratory studies and to variations in the processes from one producer to another, and even from batch to batch.…”
Section: Hydrothermal Stabilitymentioning
confidence: 79%
“…The volume expansion in stabilized zirconia due to the tetragonal to monoclinic phase transformation has advantages and drawbacks . The metastable tetragonal structure transforms to the monoclinic structure under stress, which results in a localized volumetric expansion that can halt a propagating crack and ultimately increase toughness by applying pressure at the crack tip . However, the resulting strain on the surrounding system causes micro‐cracks by expanding the surface area, leading to a rougher zirconia surface .…”
Section: Introductionmentioning
confidence: 99%